Persepsi Mahasiswa terhadap Infrastruktur Pendidikan dan Integrasi Computational Thinking di Perguruan Tinggi - M. Nurul Fajri; Ruslan Kadir; Putri Nirmala; Rachmawaty Kadir; Rahmawati (Academic Bright Collaboration, 2025)
The disparity in educational infrastructure across universities in Indonesia presents a significant barrier to the integration of computational thinking (CT) in higher education. This study aims to explore students’ perceptions of educational infrastructure development and the integration of CT in university learning. A descriptive quantitative method was employed using a Likert-scale questionnaire distributed to 73 university students. The results show that students perceive CT as highly relevant for enhancing critical thinking and problem-solving skills, with strong support for its integration into curricula. However, perceptions regarding the adequacy of educational infrastructure in Indonesia remain neutral to negative. Students also highlighted the importance of teacher and parent roles, as well as equitable access to professional training for successful CT implementation. These findings suggest that while awareness of CT’s relevance is high, systemic improvements in infrastructure and educator capacity are essential to support effective implementation in higher education.